Strategies in physical education and their impact on student intensity, perceptions, and engagement - Gonçalves, M. J.R.; Oliveira, G.; Ramos, S. P.; Venancio, E. J.; Goldberg, T. B.L. [UNESP]; Silva, C. C. (My University, 2024)
Purpose. Previous research indicates that physical education (PE) classes frequently fail to meet the recommended levels of moderate to vigorous physical activity (MVPA). This study aimed to compare the intensity levels achieved through different PE strategies, and, as a secondary objective, to evaluate students' perceptions of fun, motivation, and engagement. Materials and Methods. A total of 52 students (23 girls and 29 boys) participated in the study. The children were healthy and none of them were taking medication continuously or presented any orthopedic physical inability that would prevent them from performing the tests. All the children attended three PE classes on separate days; a recreational strategy, a circuit-based high-intensity interval training (circuit/HIIT) class, and a traditional class. All classes included games and activity content that followed the country's guidelines. Intensity levels were measured using portable heart rate (HR) monitors, and perceived exertion was assessed using the rate of perceived exertion (RPE) scale. For comparisons between each class strategy, the Kruskal-Wallis test and Dunn´s test were used to identify significant differences (P<0.05). Qualitative data are presented as percentages of interview responses. Results. All strategies led to a level of engagement in MVPA for more than 50% of the total class duration. The circuit/HIIT and recreational strategies demonstrated significantly higher proportions of time spent in MVPA compared to the traditional class (P<0.01). The qualitative results showed that the recreational class received the highest number of positive responses, followed by the traditional class, while the circuit/HIIT received fewer positive responses. In addition, the RPE values aligned with the quantitative HR results, reflecting the class intensities. Conclusion: The circuit/HIIT strategy achieved the highest percentage (93.2%) of time in MVPA, followed by the recreational (91.8%) and traditional classes (77.6%). The results highlight the excellent percentage of time spent in MVPA in the recreational strategy, and qualitatively, the higher levels of fun, motivation, and engagement among students in this model. Thus, the recreational strategy led to excellent intensity of activity during the class, as well as positive responses in relation to the students' motivation and engagement.
Keywords: Child; healthy, heart rate; physical exertion